Legal Aspects of International Cooperation Between Countries on Terrorism Criminal Action: Human Rights Perspective - Juanrico Alfaromona Sumarezs Titahelu (JURNAL BELO, 2022)
Terrorism has become a worldwide concern since the events of September 11, 2001, in the United States, in addition to the Bali bombings in Indonesia in 2002 and the bombings at Davao City airport in 2003. The broad impact of terrorism has caused Indonesia and the regional countries of Southeast Asia to feel very interested in actively participating in solving this problem. Forums for discussion and cooperation in the fight against terrorism have also arisen in the Southeast Asian region, such as the ASEAN Ministerial Meeting on Transnational Crime (AMMTC), which is a meeting forum within ASEAN to discuss issues of transnational crime. The purpose of this document is to examine and discuss the legal aspects of international cooperation in efforts to combat criminal acts of terrorism. The method that the researcher uses is a normative method, which uses a statutory approach, a case approach, and a conceptual approach. The technique of collecting legal materials used is by reviewing, identifying, and classifying primary and secondary legal materials based on library research. Then, the researcher describes qualitative description. Terrorism is all forms of actions and attitudes that are directly implemented against a country with the aim of creating terror against certain persons, groups, individuals, or the wider community. International cooperation between countries in order to maintain security against counter-terrorism crimes in ASEAN is necessary for achieving dynamic peace and stability while still prioritizing Indonesia's national interests which will also support the creation of an ASEAN Community in 2015 which consists of three mutually supportive principles, including the political-security community, the economic community, and the social and cultural community. The legal aspects of international cooperation between countries in efforts to combat terrorism include preventive, preventive, and repressive measures.